Liberation via Reliving the Suffering: A Study of August Wilson’s Monologues - Sumita; Mayur Chhikara (IAFOR Journal of Arts & Humanities)
The articulation of counter-discourse has long served as a central mechanism for expressing resistance, resilience, and the reclamation of histories centered on marginalized communities. Human history attests to the fact that speech has consistently functioned as a foundational step toward liberation. Yet, the concept of speech extends far beyond the public oratory of a select few prominent social or political figures. Instead, the everyday dialogues of ordinary individuals often carry a more substantial share of the transformative and emancipatory ideas emerging from marginalized communities. Within these dialogues, monologues emerge as a powerful medium for articulating the firsthand experiences of the oppressed. This paper undertakes a deconstructive analysis of the monologues in select plays by August Wilson, interpreting them through the lens of Freud’s theory of repression. It explores how African American characters, through the act of monologue, relive their collective and individual suffering, thereby equipping themselves with greater readiness and resilience to envision and strive for a liberated future. The study positions these monologues as literary instruments of healing, examining them through the framework of speech act theory. Ultimately, the monologues are analyzed as expressions of resilience and liberation, offering both textual catharsis and a reassertion of identity within a broader sociocultural context.